Comparative Evaluation of Conventional Stool Testing and Multiplex Molecular Panel in Outpatients With Relapse of Inflammatory Bowel Disease. Issue 10 (2nd January 2021) - Hong, Soonwook; Zaki, Timothy A; Main, Michael; Hine, Ashley M; Chang, Shannon; Hudesman, David; Axelrad, Jordan E
Abstract: Background: Differentiating between enteric infection and relapse of inflammatory bowel disease (IBD) is a common clinical challenge. Few studies have evaluated the impact of multiplex gastrointestinal polymerase chain reaction (GI PCR) pathogen panels on clinical practice compared to stool culture. Our aim was to compare the impact of PCR stool testing to conventional stool testing in outpatients presenting with relapse of IBD. Methods: In a retrospective cohort study of outpatients with IBD presenting to NYU Langone Health with flare from September 2015 to April 2019, we compared patients who underwent stool testing with GI PCR to age-, sex-, and IBD-subtype-matched patients who underwent culture and ova and parasite exam (conventional testing). The primary outcome was IBD therapy escalation after testing. Secondary outcomes included rates of posttesting endoscopy, abdominal radiography, antibiotics, and IBD-related emergency department visits, hospitalizations, and abdominal surgeries. Results: We identified 134 patients who underwent GI PCR matched to 134 patients who underwent conventional testing. Pathogens were more frequently identified on GI PCR (26 vs 5%; P  < 0.01). We found that GI PCR was associated with less escalation in IBD therapy (16 vs 29%; P  < 0.01) and fewer posttest endoscopies (10% vs 18%; P  = 0.04), with no differences in IBD outcomes. On multivariate analysis, testing with GI PCR was associated with an odds ratio of 0.26 (95% confidence interval, 0.08-0.84; P  = 0.02) for escalation of IBD therapies. Conclusions: Testing with GI PCR was associated with higher rates of pathogen detection and lower rates of IBD therapy escalation and endoscopy in the outpatient setting. These changes in management were not associated with a difference in IBD outcomes.